Acupuncture Treatment Reverses Retinal Gene Expression Induced by Optic Nerve Injury via RNA Sequencing Analysis - Chen, Jie; Zhang, Li; Liu, Lanying; Yang, Xueqin; Wu, Fengzhi; Gan, Xiulun; Zhang, Rong; He, Yinjia; Lv, Qiuyi; Fu, Haonan; Zhou, Ling; Zhang, Jiaxi; et al. (Frontiers in Integrative Neuroscience, 2019)
Glaucoma and traumatic optic nerve crush (ONC) injury result in progressive loss of retinal ganglion cells (RGCs) and defects in visual function. In clinical trials of Traditional Chinese Medicine, acupuncture has been widely used for the treatment of ocular diseases. However, the molecular mechanisms of acupuncture treatment are still unclear. In this study, we used technique of RNA sequencing (RNA-seq) to study the effects of acupuncture treatment on retinal transcriptome after axotomy injury. RNA-seq results revealed that 436 genes including 31 transcription factors (TFs) were changed after injury, among them were many well-known neural degeneration related TFs such as Jun, Ddit3, Atf3 and Atf4. Interestingly, acupuncture treatment at acupoint GB20 (Fengchi) significantly reversed a series of differential expressed genes (DEGs) induced by optic nerve injury. While treatments at BL1(Jingming) or GB20 sham control acupoint-GV16 (Fengfu), led to limited DEG reversal. In contrast, treatments at these two sites further enhanced the trend of DEG expression induced by axotomy injury. At last, retina immunostaining results revealed that only GB20 acupoint treatment increased RGC survival, in consistent with RNA-seq results. Therefore, our study first reported that acupuncture treatment regulated retinal transcriptome and reversed the gene expression induced by axotomy injury, and GB20 acupoint treatment increased RGC survival, which will provide novel therapeutic targets for treatment of ocular diseases.